PENGARUH ETIKA TERHADAP KEGIATAN PELAYANAN JASA PENGIRIMAN EKPEDISI WAHANA - Astrid Virly Maharani; Ari Susanto (PUTRA JAWA PUBLISHER, 2023)
Ethics serves as a framework for various human actions. The study of value today is more about what is meant by ethics. One of the top businesses in the sector is low-cost delivery services under the brand name Wahana Express, logistics and warehousing under the name Wahana Logistic, and e-commerce assistance (Wahana Commerce). Wahana has more than 20 years of experience serving the nation and is poised for dynamic growth in the industry 4.0 era with affordable, fast, and friendly services. Existing customer satisfaction serves as a benchmark for business sustainability efforts. This can be measured by the reaction of the community or existing customers, which can be positive or negative. In addition, marketing can be done by someone introducing some new things that are fairly innovative or new thoughts in terms of some delivery, both on products and services in order to generate interest on the part of consumers. With many people using the internet today, a number of purchases will be made of goods found on e-commerce sites, and delivery will be made using available delivery services. The customer side will likely observe certain principles, such as those used in businesses that provide services to customers while understanding their needs.